2017
DOI: 10.1080/14756366.2017.1279155
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and in vitro anti-proliferative activity of some novel isatins conjugated with quinazoline/phthalazine hydrazines against triple-negative breast cancer MDA-MB-231 cells as apoptosis-inducing agents

Abstract: Treatment of patients with triple-negative breast cancer (TNBC) is challenging due to the absence of well- defined molecular targets and the heterogeneity of such disease. In our endeavor to develop potent isatin-based anti-proliferative agents, we utilized the hybrid-pharmacophore approach to synthesize three series of novel isatin-based hybrids 5a–h, 10a–h and 13a–c, with the prime goal of developing potent anti-proliferative agents toward TNBC MDA-MB-231 cell line. In particular, compounds 5e and 10g were t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
44
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(49 citation statements)
references
References 59 publications
1
44
0
Order By: Relevance
“…Isatin (1H-indole-2,3-dione) is an endogenous compound in certain organisms and it was discovered in 1988 [2]. It received considerable attention in the medicinal arena because it is included in a number of bioactive heterocyclic compounds with diverse pharmacological profiles [3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Isatin (1H-indole-2,3-dione) is an endogenous compound in certain organisms and it was discovered in 1988 [2]. It received considerable attention in the medicinal arena because it is included in a number of bioactive heterocyclic compounds with diverse pharmacological profiles [3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…A representative example of an already developed isatin-based anticancer drug is sunitinib (I, Sutent™, Pfizer, Inc. New York, NY, USA, Figure 1), which was granted FDA approval in 2006 as an orally active profiles [3][4][5][6][7][8]. A representative example of an already developed isatin-based anticancer drug is sunitinib (I, Sutent™, Pfizer, Inc. New York, NY, USA, Figure 1), which was granted FDA approval in 2006 as an orally active multi-targeted tyrosine kinase inhibitor used for the management of imatinib-resistant gastrointestinal stromal tumors and metastatic renal-cell carcinoma [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…The isatin–quinazoline hybrids 42 (Figure 7; IC 50 : 1.0 to >100 μM, SRB assay) showed certain activity against MCF‐7, HepG2, HT‐29, and MDA‐MB‐231 cancer cell lines and only hybrids 42a,b (IC 50 : 1.0‐26 μM) were sensitive to the tested three cancer cell lines. [ 98,99 ] The activity of hybrids 42a,b (IC 50 : 1.0 and 1.8 μM) was superior to that of doxorubicin (IC 50 : 2.9 μM) against HepG2 cells, but (IC 50 : 7.4 and 9.8 μM) comparable to that of sunitinib (IC: 6.8 μM) against MCF‐7 cells. Further study revealed that these hybrids could induce apoptosis in HepG2 cells since they could enhance the expression of the pro‐apoptotic protein Bax and reduce expression of the antiapoptotic protein Bcl‐2, in addition to increase caspase‐3 levels.…”
Section: Isatin–coumarin Hybridsmentioning
confidence: 99%
“…Based on the aforementioned findings and in connection with our research program on the development of indolin-2-one-based anticancer candidates [14][15][16][17][18][19][20][21][22] , it was thought worthwhile to extend our investigations to probe certain hydrazonoindolin-2-ones displaying promising anti-proliferative activity. In this study, we reported the design and synthesis of different series of hydrazonoindolin-2-ones 3a-e, 5a-e, 7a-c, and 10a-l, adopting three distinctive strategies to develop such derivatives (Figure 2).…”
Section: Introductionmentioning
confidence: 99%
“…It is a multikinase inhibitor that targets VEGFR-1, VEGFR-2, PDGFRb, and c-Kit. Recently, our research group has paid much attention to develop many novel small molecules based on the indolin-2-one core as potent anticancer agents [14][15][16][17][18][19][20][21][22] . In 2017, we reported two studies 14,15 regarding development of hydrazonoindolin-2-onebased derivatives and evaluation of their anti-proliferative activity against A549 (lung), HT-29 (colon), and ZR-75 (breast) human cancer cell lines, beside evaluation of their pro-apoptotic activity.…”
Section: Introductionmentioning
confidence: 99%